PERAN KADAR HEMOGLOBIN PADA KEBUGARAN JASMANI REMAJA - Fadilah, Tersanova; Adriani, Donna (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2023)
Physical fitness becomes a problem in Indonesia because it is categorized in the poor category, especially for adolescents aged 10-19 years. Adolescents are expected to have good physical fitness as they are about to enter productive age. Physical fitness is defined as the ability of a person to perform daily physical tasks optimally, even doing several additional physical activities without causing significant fatigue. Factors that affect a person's physical fitness consist of internal and external factors. Internal factors refer those that have settled from within the body such as genetics, age, and gender. Meanwhile, external factors include physical activity, nutritional status, health status, adequate rest, smoking habit, and haemoglobin levels. Haemoglobin is a protein complex consisting of haeme and globin, rich in iron, and whose function is to carry oxygen from the lungs to body tissues or throughout the body. Anaemia define when the haemoglobin levels in a person's blood is lower than normal. Anaemia is a problem in various communities all over the world, especially in developing countries such as Indonesia. According to the Ministry of Health of Indonesia in 2013, the prevalence rate of anaemia in all age groups was 21.70%. Symptoms of low haemoglobin levels are weakness, fatigue, poor work productivity, and difficulty in concentrating. This mechanism is caused by decreased oxygen uptake and reduced oxygen capacity to be transported to body tissues, affecting physical fitness. This literature review discusses the role of haemoglobin levels in physical fitness, in order to improve physical fitness.